Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Bangun Datar Berdasarkan Prosedur Newman Pada Kelas IV SD Negeri Talamau Pasaman Barat - Resi Delfita; Susi Herawati; Listy Vermana (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2023)
This research was conducted because there were still many students making mistakes in solving flat word problems and it aims to describe students' mistakes in solving flat word problems based on Newman's procedure and to describe the factors that cause students to make mistakes. The subjects of this research were the fourth grade students of SD Negeri 17 Talamau, which consisted of 3 students. Data was collected by giving essay tests in the form of story questions and interviews and analyzed through three stages, namely data reduction, data presentation and conclusions. The results showed that (1) high-ability subjects made mistakes in understanding the problem, processing skills and writing the final answer (2) moderate-ability subjects made transformation mistakes, process skills and wrote the final answer (3) low-ability subjects made mistakes in reading the questions, errors understanding the problem, transformation, process skills and writing the final answer. The percentage of types of student errors based on the Newman procedure (1) 23% reading errors, 54% understanding errors, 59% transformation errors, 75% processing skills errors, and 77% final answer writing errors. Factors that cause students to make mistakes are (1) the lack of students' ability to read questions (2) forgetting to write down what is known and being asked in questions (3) not being thorough in writing formulas (4) not being able to input what is known into mathematical formulas (5) forgetting to write down conclusion.